Storage Potential of Cactus Mucilage Powder for Incorporation into Foods and Production of Biopolymeric Films - Souza, Jheizon Feitoza do Nascimento [UNESP]; Andrada, Lucas Vinícius Pierre de; Martins, Lady Daiane Costa de Sousa; Brito, Andréa Monteiro Santana Silva; Silva, Lúcio José Vieira; Silva, Ivo Diego de Lima; Vinhas, Glória Maria; Silva, Thieres George Freire da; Simões, Adriano do Nascimento (American Chemical Society (ACS), 2024)
The objective was to investigate the physicochemical stability of stored cactus pear mucilage and assess the technological feasibility to produce polymeric films. Mucilage of cactus pear species Nopalea cochenillifera (L.) Salm-Dyck MIU and Opuntia stricta (Haw.) Haw─OEM was extracted and stored for 2, 4, 6, 8, and 10 months in the absence of light at a temperature of 26.5 °C and relative humidity of 41.3%. At each storage time, polymeric films were produced using hydrated mucilage (4%, weight─w/volume─(v)), glycerol (60%, v/v), and calcium lactate (2%, w/v). Among the species, MIU stood out due to its higher water and oil retention, but it also presented higher levels of phenolic compounds, and more intense peaks in Fourier transform infrared spectrophotometry (FTIR) analysis. On the other hand, OEM is richer in carbohydrates, denser, and electrically conductive. The characteristics highlighted for each species are also observed in the principal component analysis (PCA). Both species are equally soluble in water, and more than 60% of their granules have a diameter of 250 mm. The resulting films of MIU exhibited increased resistance and permeability but were less soluble and transparent. Microscopically, greater homogeneity was observed, and the films were thicker, whitish, and thermally stable. Both species have the potential for producing polymeric films with various applications in the food industry, particularly as edible coatings.